A methodology for estimation of site-specific nonlinear dynamic soil behaviour using vertical downhole arrays - Eseller-Bayat, E. Ece; Ada, Mehmet (Informa UK Limited, 2019)
System identification (SI) techniques have been widely used in Geotechnical Engineering to understand the characteristics of soils. In this study, system identification techniques with and without ...